Comparison between two molar incisor hypomineralization detection criteria in epidemiological surveys - Mendonça, Fernanda Lyrio; Regnault, Fabiana Giuseppina Di Campli; Grizzo, Isabella Claro; Martins, Daiana da Silva; Fragelli, Camila [UNESP]; Leal, Soraya Coelho; Honório, Heitor Marques; Rios, Daniela (Wiley, 2024)
Background: There is no consensus on which molar incisor hypomineralization (MIH) indices are more suitable for epidemiological surveys. Aim: To compare the operational aspects and diagnostic ability of the MIH index (simplified/MIH_s and extended/MIH_e) with the MIH-Severity Scoring System (MIH-SSS) in classifying and diagnosing MIH. Design: This cross-sectional study assessed the indices in a homogeneous group of 680 6- to 10-year-old schoolchildren in Bauru, Brazil, who had at least one first permanent molar, ensuring consistent conditions. Followed by toothbrushing, the children seated on school chairs were examined by the two calibrated researchers under artificial lighting, using mouth mirror and WHO probe, and chronometer recording the duration of examinations. Results: The prevalence of MIH was 24.7%. The most common characteristic of MIH was demarcated opacity, with a prevalence of 81.7% and 85.45% according to the MIH_s and the MIH-SSS, respectively. A positive association was observed among the MIH_s, the MIH_e, and the MIH-SSS (chi-squared test; p <.01). The MIH-SSS demonstrated a shorter average application time than both versions of the MIH index (ANOVA/Tukey; p <.05). Additionally, fluorosis was found to be the most prevalent among other developmental defects of enamel, with a prevalence of 38.38%. Conclusion: All systems effectively diagnosed MIH and its characteristics.
Keywords: epidemiological surveys; epidemiology; MIH index; MIH-SSS; molar incisor hypomineralization